Needs Assessment for Professional Competence of Elementary School Teacher in Yogyakarta - Mirsa, Nur Rina Priyani (IJCAR: Indonesian Journal of Classroom Action Research, 2024)
This research investigates the gaps in professional competence among teachers, focusing on the five key dimensions: interpersonal skills, work-related motivation, self-regulation, professional beliefs, and pedagogical content knowledge. The research utilizes a comprehensive analysis and synthesis of literature, validated by seven experts in educational administration, to identify the priority areas for development. A survey questionnaire was employed to 238 teachers to measure the level of professional competence gaps in Kabupaten Sleman, Yogyakarta. A Priority Needs Index (PNI) modified was calculated to analyze the data. The findings reveal that interpersonal skills have the highest Priority Needs Index (PNI) value of 0.932, indicating a critical need for improvement in collaboration with parents and community members. Work-related motivation and self-regulation follow as significant areas requiring attention, with PNI values of 0.462 and 0.398, respectively. The research emphasizes the interconnected nature of these dimensions, suggesting that enhancing interpersonal skills can positively impact other areas of professional competence.